2022
DOI: 10.1155/2022/3656932
|View full text |Cite
|
Sign up to set email alerts
|

Processing Agroindustry By-Products for Obtaining Value-Added Products and Reducing Environmental Impact

Abstract: Over four billion tons of foods are produced annually on the planet, and about a third is wasted. A minimal part of this waste is incinerated or sent to landfills for treatment, avoiding contamination and diseases; the rest is disposed of elsewhere. The current review was aimed at broadening the panorama on the potential of agroindustrial by-products in applications such as biofuels, biomaterials, biocompounds, pharmaceuticals, and food ingredients. It also exposes the main chemical, physical, and biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Before the process of valorization, organic matter was transformed or the compound was extracted using a variety of physical, chemical, or biological procedures known as pre-treatment operations as depicted in Fig. 5 [3] , [35] . Other than assisting the procedure of bioconversion of the biomass feedstock through pretreatment, ultrasound energy is also utilized in the valorization process by combining the existing valorization technology with ultrasonic processes.…”
Section: Role Of Ultrasound Technology In the Conversion Of Agricultu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Before the process of valorization, organic matter was transformed or the compound was extracted using a variety of physical, chemical, or biological procedures known as pre-treatment operations as depicted in Fig. 5 [3] , [35] . Other than assisting the procedure of bioconversion of the biomass feedstock through pretreatment, ultrasound energy is also utilized in the valorization process by combining the existing valorization technology with ultrasonic processes.…”
Section: Role Of Ultrasound Technology In the Conversion Of Agricultu...mentioning
confidence: 99%
“…These by-products are produced predominantly during the harvesting operation, storage, shipping, industrial processing, packaging, wholesale and retail, domestic utilization, etc. To date, it is reported that many agro-based by-products are underutilized or untreated for better disposal which negatively affected human and animal health [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Processing new by-products can be economically challenging because of the initial investment required and competition with established low-cost products. Therefore, it is important to explore value-added products or co-products that can be generated from these by-products, and consequently, market these high-value ingredients to increase revenue [81]. In addition, the processing of large quantities of heterogeneous raw materials may require investments in flexible and scalable processing units.…”
Section: Optimization Of Lipase Production Using a Ccrd (2 3 )mentioning
confidence: 99%
“…Some clinical trials have already demonstrated the beneficial effects of carotenoid consumption by patients with IBD [12,13]. Derived from primary and secondary activities of agro-industrial processes [14], by-products of different plants, such as cashew, constitute an interesting source of carotenoids [15][16][17].…”
Section: Introductionmentioning
confidence: 99%